Aberrant Cerebellar Resting‐State Functional Connectivity Related to Reading Performance in Struggling Readers. Issue 2 (27th August 2020) - Greeley, Brian; Weber, Rachel C.; Denyer, Ronan; Ferris, Jennifer K.; Rubino, Cristina; White, Katherine; Boyd, Lara A.
Abstract: Reading is a critical neurodevelopmental skill for school‐aged children, which requires a distributed network of brain regions including the cerebellum. However, we do not know how functional connectivity between the cerebellum and other brain regions contributes to reading. Here we used resting‐state functional connectivity to understand the cerebellum's role in decoding, reading speed, and comprehension in a group of struggling readers (RD) and a group of adolescents and children with typical reading abilities (TD). We observed an increase in functional connectivity between the sensorimotor network and the left angular gyrus, left lateral occipital cortex, and right inferior frontal gyrus in the RD group relative to the TD group. Additionally, functional connectivity between the cerebellum network and the precentral gyrus was decreased and was related to reading fluency in the RD group. Seed‐based analysis revealed increased functional connectivity between crus 1, lobule 6, and lobule 8 of the cerebellum and brain regions related to the default mode network and the motor system for the RD group. We also found associations between reading performance and the functional connectivity between lobule 8 of the cerebellum and the left angular gyrus for both groups, with stronger relationships in the TD group. Specifically, the RD group displayed a positive relationship between functional connectivity, whereas the TD group displayed the opposite relationship. These results suggest that the cerebellum is involved in multiple components of reading performance and that functional connectivity differences observed in the RD group may contribute to poor reading performance. Abstract : A group of struggling readers and aged‐matched controls were scanned and separately performed a battery of reading tests. We observed decreased functional connectivity between the cerebellum network and the precentral gyrus, and increased connectivity between crus 1, lobule 6 and 8 of the cerebellum and the motor system in the struggling readers. We also found several associations between reading performance (decoding, fluency, and comprehension) and functional connectivity in both groups, suggesting that the abnormal functional connectivity differences observed in the struggling readers may contribute to poor reading performance.